Knowledge of oral cancer, preventive attitudes, and behaviors of primary care physicians in Turkey - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Oral cancers (OCs) have a high mortality rate because of their typically late diagnosis. Primary care physicians play a vital role in early detection. In this study, we evaluated the family physicians' (FPs) knowledge, preventive attitudes, and behaviors in terms of OCs. A semistructured questionnaire consisting of 50 questions was prepared and distributed to 200 FPs. Questions were grouped under four main headings: demographic characteristics, general protective attitudes against OCs, risk factors, and daily practices while performing the necessary examinations and referrals. Of 200 FPs, 164 responded to the questionnaire (82% response rate). The mean age of the study participants was 34.8 +/- 8.4 years and the mean duration of practice was 10 +/- 8.1 years. One-third of the physicians (29.9%, n = 49) stated that they did not inquire about the amount of tobacco use. In terms of alcohol use, 45.7% (n = 75) and 56.7% (n = 93) did not ask about past alcohol consumption or the amount of alcohol consumed, respectively. Moreover, 69.5% (n = 114) believed that they did not receive adequate smoking cessation training and 79.9% (n = 131) stated that they did not receive any alcohol cessation training. To decrease morbidity and mortality associated with OCs, primary care physicians should be trained to ask their patients about high-risk behaviors, provide counseling and education on tobacco and alcohol-abuse cessation, and provide oral examinations. (c) 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: behavior; family physicians; knowledge; oral cancers; prevention; DENTISTS; ETIOLOGY; LESIONS